The Dynamics of Broiler Meat Supply in South Africa and Its Implications for Achieving SDG 2: Zero Hunger - Gabriel Mmila; Lindikaya W. Myeki (Agriculture)
Broiler meat remains an important source of food with immense potential for ending hunger as well as achieving food and nutrition security (SDG 2). We apply the Autoregressive Distributed Lag (ARDL) model to time-series data spanning from 2010 to 2021 to ascertain the response of South Africa’s broiler meat supply to changes in imports, exports, and inflation. The results show that broiler supply from local producers is negatively affected by the quantity of broiler meat imported. For every unit increase in broiler meat imports, domestic broiler supply decreases by −0.12% in the long run. However, in the short run, for every 1% increase in the broiler imports, there is an increase of 0.07% in domestic broiler supply. The supply of domestic broiler meat increases by 0.37% for every 1% increase in the consumer price index in the long run, while the unit increase in the consumer price index is associated with a decrease of 2.12 in domestic broiler supply in the short run. In the short run, broiler exports have a positive relationship with domestic broiler supply. A unit increase in broiler exports is associated with a 0.04 increase in the domestic broiler supply. The earlier finding could allow for greater development of the local broiler industry through South Africa’s Poultry Masterplan, by increasing domestic broiler meat supply to discourage imports and to increase broiler exports contributing to the pressing need for job creation and food security, but the latter can exact an inhibiting effect on the accessibility of broiler meat. We concluded that the attainment of SDG 2 in South Africa is possible if policy strikes a balance between food availability and accessibility, particularly when it comes to broiler meat as it is the cheapest source of protein. This could be achieved through increased investment towards expanding domestic broiler production and promoting strategies for reasonable pricing of poultry, while giving priority to consumer health concerns.